POTENTIAL OF CITRUS LEAF EXTRACT (Cymbopogon citratus (DC.) Stapf) AS AN ANTIBACTERIAL INHIBITORY of Staphylococcus epidermidis - Karnelasatri, Karnelasatri; Cenwira, Wishia; Andareas, Pangeran; Santoso, Feronia Reni Cyrena (Jurnal Insan Farmasi Indonesia, 2023)
The concerns of antibiotic resistance have increased in recently years, this issue caused by long-term repeated use of antibiotics to treat bacterial illnesses. Lemongrass leaf (Cymbopogon citratus (DC.) Stapf) is one of the natural ingredients that can be used as an alternative antibacterial. The study objective is to determine the antibacterial activity of the ethanol extract of 70% cooking leaves against Staphylococcus epidermidis using diffusion methods. In addition, the Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) of extracts were determined using liquid dilution methods. The results of this study show that extract concentrations of 1,000,000 ppm have a barrier zone in the intermediate category when compared with the positive control, that is, clindamycin. Meanwhile, the MIC value obtained is 1250 ppm, while the MBC value is 5000 ppm. The results of statistical analysis showed that there were no significant differences in the inhibition zone diameter formed between the test concentrations.